Effectiveness of the acute stroke care map program in reducing in-hospital delay for acute ischemic stroke in a Chinese urban area: an interrupted time series analysis - Wen, Rui; Wang, Miaoran; Bian, Wei; Zhu, Haoyue; Xiao, Ying; Zeng, Jing; He, Qian; Wang, Yu; Liu, Xiaoqing; Shi, Yangdi; Hong, Zhe; Xu, Bing (Frontiers in Neurology, 2024)
Background Timely intravenous thrombolysis (IVT) is crucial for improving outcomes in acute ischemic stroke (AIS) patients. This study evaluates the effectiveness of the Acute Stroke Care Map (ASCaM) initiative in Shenyang, aimed at reducing door-to-needle times (DNT) and thus improving the timeliness of care for AIS patients. Methods An retrospective cohort study was conducted from April 2019 to December 2021 in 30 hospitals participating in the ASCaM initiative in Shenyang. The ASCaM bundle included strategies such as EMS prenotification, rapid stroke triage, on-call stroke neurologists, immediate neuroimaging interpretation, and the innovative Pre-hospital Emergency Call and Location Identification feature. An interrupted time series analysis (ITSA) was used to assess the impact of ASCaM on DNT, comparing 9 months pre-intervention with 24 months post-intervention. Results Data from 9,680 IVT-treated ischemic stroke patients were analyzed, including 2,401 in the pre-intervention phase and 7,279 post-intervention. The ITSA revealed a significant reduction in monthly DNT by −1.12 min and a level change of −5.727 min post-ASCaM implementation. Conclusion The ASCaM initiative significantly reduced in-hospital delays for AIS patients, demonstrating its effectiveness as a comprehensive stroke care improvement strategy in urban settings. These findings highlight the potential of coordinated care interventions to enhance timely access to reperfusion therapies and overall stroke prognosis.